Are there Any Differences in Simple and Random Choice Motor Task Performance between Young and Middle-Aged Adults? - Rima Solianik; Vaida Aleknavičiūtė; Albertas Skurvydas; Marius Brazaitis (Lithuanian Sports University, 2018)
Research background and hypothesis. Most studies are based on elderly subjects' results, so there is a need to explore if motor performance changes begin in the middle age. We hypothesize that (i) middle-aged subjects use "play it safe" strategy, which depends on the type of tasks (simple vs. random choice); (ii) middle-aged subjects will show higher intra-individual performance variability compared to young adults, furthermore, simple task will show  lower performance variability. Research aim was to establish if there were any movement performance differences during simple and random  choice motor task performance between young and middle-aged adults. Research methods. Middle-aged and young adults performed two speed-accuracy tasks. During simple task  participants had to reach the same target which appeared in the same place and during random choice task the target  appeared randomly in one of the three different places. Research results. Data showed that middle-aged group had slower (p < 0.05) reaction time and maximal velocity,  whereas movement path length was more accurate (p < 0.05) than that in the young adult group. Comparing different  tasks it was observed that during simple task reaction time was faster (p < 0.05) than in the random choice task in  both groups. Intra-individual variability of reaction time and maximal velocity was higher (p < 0.05) in the middle-aged group, whereas no changes were observed between different tasks. Discussion  and  conclusion.  Motor  performance  strategy  "play  it  safe"  is  already  observed  for  the  middle- aged population: they decrease maximal velocity and reaction time in order to make movement more accurate.  Additionally, they demonstrate task-independent higher intra-individual variability of reaction time and maximal  velocity showing changes in CNS integrity compared to young adults. Keywords: aging, speed-accuracy tasks, intra-individual variability.